Prevalence and Clinical Features of FOG in Chinese PD Patients, a Multicenter and Cross-Sectional Clinical Study - Gan, Jing; Liu, Weiguo; Cao, Xuebing; Xie, Anmu; Li, Wentao; Yuan, Canxing; Jin, Lirong; Liu, Suzhi; Jin, Lingjing; Guo, Dengjun; Shen, Yuefei; Wu, Yuncheng; et al. (Frontiers in Neurology, 2021)
Objectives: Freezing of gait (FOG) is generally considered as an independent symptom of Parkinson’s disease (PD) with a complex pathophysiology. There is a wide range of associated clinical features of FOG reported from different studies without consistent conclusion. Thus, a multicenter, cross-sectional study was designed to investigate the prevalence and clinical features of FOG together with its unique contribution quality of life in Chinese PD patients. Methods: 838 PD patients were consecutively recruited into this study from 12 hospital centers in 6 provinces, China. Clinical information , including motor and neuropsychological features as well as pharmacological details，was collected. Results: Of 827 PD patients, 245 (29.63%) reported FOG. The prevalence of FOG was strongly correlated with modified H-Y stages and symptomatic duration (p < 0.01). 84.90% freezers experienced FOG during turning and 88.98% experienced when initiating the first step. Compared with non-freezers, freezers reported longer disease duration (7.73±5.44 versus 4.69±3.94, p < 0.000), higher frequent PIGD phenotype (61.22% versus 35.91%, p < 0.000), higher scores of UPDRS III (32.85±15.47 versus 22.38±12.89, p < 0.000), HAMA (10.99±7.41 versus 7.59±6.47, p < 0.000), HAMD (15.29±10.29 versus 10.58±8.97, p < 0.000) and lower MMSE score (25.12±5.27 versus 26.63±3.97, p < 0.000), and higher daily levodopa dosage (432.65±264.31 versus 319.19±229.15, p < 0.000) with less frequent initial use of dopaminergic agonist (8.57% VS 14.78%, p < 0.05). Using binary logistic regression, the associated factors of FOG might be non-tremor dominant onset (OR=3.817, p < 0.000), the presence of anxiety (OR=2.048, p < 0.000) and imbalance (OR=4.320, p = 0.012). Freezers had poorer quality of life than non-freezers and FOG impacted PDQ-8 independently. Conclusion: Nearly one third PD patients experienced FOG. Its frequency increased with PD progression and FOG reduced independently the quality of life. Non-tremor dominant, disease progression and anxiety were risk factors of FOG.